Did COVID-19 (Permanently) Raise the Demand for "Teleworkable" Jobs? - Massimiliano Bratti; I. Brunetti; A. Corvasce; Agata Maida; Andrea Ricci (Institute of Labor Economics (IZA), 2024)
This study leverages detailed administrative data on firms' job flows and variation across Local Labor Markets (LLMs) in the spread of COVID-19 to investigate shifts in labor demand prompted by the pandemic. To this end, we exploit the large spatial variation in the intensity of the pandemic observed in Italy. Namely, we investigate the effect of COVID-19 intensity on the composition of new hires in terms of jobs suitable for "working from home" (WFH), which emerged as a new standard during the pandemic. Our results reveal a significant increase in teleworkable-job hires in LLMs that were more severely hit by the pandemic, primarily driven by permanent contracts. An event study analysis uncovers substantial heterogeneity over time. Indeed, the effect was short-term and lasted only for two semesters after the pandemic's outbreak. Although this shift was transitory, by involving permanent hires, it had persistent effects on the structure of the workforce. An effect-heterogeneity analysis shows that effects were greater on the demand for female and younger workers and hires of larger firms, of service firms, and of those located in Northern Italy.
Keywords: D22; J23; J24; 330; working from home; telework; labor demand; COVID-19; Italy